1980
DOI: 10.1128/aac.17.5.803
|View full text |Cite
|
Sign up to set email alerts
|

2'-fluoro-5-iodo-aracytosine, a potent and selective anti-herpesvirus agent

Abstract: A newly synthesized pyrimidine analog, 2'-fluoro-5-iodo-aracytosine (FIAC), suppressed by 90% the replication of various strains of herpes simplex virus types 1 and 2 at concentrations of 0.0025 to 0.0126 ,M. Cytotoxicity was minimal, as determined by trypan blue dye exclusion with normal Vero, WI-38, and NC-37 cell proliferation; the 50% inhibitory dose was 4 to 10 ,uM in a 4-day assay. When compared with other antiviral drugs, FIAC was active at much lower concentrations than arabinosylcytosine, iododeoxyuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
66
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(69 citation statements)
references
References 13 publications
3
66
0
Order By: Relevance
“…At 0.10 ,uM a 90% inhibition of viral DNA synthesis was obtained, whereas cellular DNA synthesis in infected cells was inhibited by 40%. However, DNA synthesis in uninfected cells was not inhibited at this concentration, and 64 ,LM FIAC was required to obtain a 50% inhibition, which confirms the results of Lopez et al (10) showing a high selectivity by FIAC when effects on HSV-1 multiplication and cytotoxicity for uninfected Vero cells were compared.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…At 0.10 ,uM a 90% inhibition of viral DNA synthesis was obtained, whereas cellular DNA synthesis in infected cells was inhibited by 40%. However, DNA synthesis in uninfected cells was not inhibited at this concentration, and 64 ,LM FIAC was required to obtain a 50% inhibition, which confirms the results of Lopez et al (10) showing a high selectivity by FIAC when effects on HSV-1 multiplication and cytotoxicity for uninfected Vero cells were compared.…”
supporting
confidence: 78%
“…BrVDU triphosphate was found to substitute for deoxy- (2,5,10). ACG seemed to be the most selective nucleoside analog when the effects on HSV-1 and cellular DNA synthesis in infected cells were compared, indicating that its triphosphate is more selective for viral DNA polymerase than the triphosphates of FIAC and BrVDU.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of equimolar concentrations of thymidine failed to reverse the antiviral activity and had no significant effect on the cytotoxicity (data not shown). A 10-fold excess of the thymidine failed to reverse the antiviral activity of FIAC and at higher concen- Our earlier studies showed that herpes simplex virus type 1-induced pyrimidine nucleoside kinase was capable of phosphorylating FIAC far better than the cellular enzymes and that this substrate preference determined, at least in part, the selective antiviral activity of this drug (18). Studies were therefore undertaken to determine whether FIAC is preferentially phosphorylated by enzymes found in cytosols from HCMVinfected rather than uninfected cells.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical management of herpes simplex virus (HSV) infections has become more effective in recent years with the introduction of selective anti-HSV drugs, such as acyclovir [9-(2-hydroxyethoxymethyl)guanine; ACV], E-5-(2-bromovinyl)-2'-deoxyuridine (BVDU), and 2'-fluoro-5-iodo-1-P-Darabinofuranosylcytosine (FIAC) (11,14,35). These drugs inhibit the replication of HSV in vitro and in vivo, while manifesting little or no toxicity.…”
mentioning
confidence: 99%